STUDI KOMPARATIF KINERJA KEUANGAN BANK NASIONAL DAN BANK ASING (Studi Kasus Pada Bank Nacional Comercio Timor Leste dan Bank Mandiri Indonesia Cabang Timor Leste ) - Barreto, Guilhermino Paulo do Santos (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.06.NO.12.TAHUN 2017DO - 10.24843/EEB.2017.v06.i12.p09, 2017)
The aim of this study was to conduct a comparative study and analysis of the financial performance of the national bank, Bank Nacional de Comercio Timor-Leste (BNCTL) and one foreign bank, namely Mandiri Bank Indonesia wich opens a branch in East Timor. The type of data was secondary data such as financial statements of BNCTL Bank and Mandiri Bank branch of East Timor in the period of 2011 – 2013. It consists of a balance sheet and income statement report/earnings. he method used was descriptive quantitative analysis with different test of two average of independent sample t-tests, with a significant level (a) = 5 %. Data analysis used software SPSS for windows. The results of the comparative study between BNCTL Bank and Mandiri branch of East Timor with different test average showed that ; 1) there was a significant performance difference between the PR ratio of  Mandiri Bank branch of East Timor and PR ratio of BNCTL where the p – value 0.021 < 0.05, 2) there was no significant performance difference between Bank Mandiri of East Timor branch and the BNCTL Bank when seen from the ratio of ROA, since the p – value 0.47 > 0.05, 3) there was a performance difference between the ratio of the LDR of Bank Mandiri of East Timor Branch and the ratio of the LDR of Bank BNCTL because the p – value was 0.037 > 0.05.